Factors Influencing Consumers’ Purchasing Intention on BerryBenka E-commerce Application in Surabaya: Applying Mediation Test of Customer Satisfaction - Sunyoto, Hadi Kusuma; Vincentia, Jennifer; Nathanael, Vincent (JURNAL STIE SEMARANG, 2024)
The increasing number of internet users globally, especially, in Indonesia, has shifted the business environment digitally. It guides to the rising numbers of e-commerce, eliminating some distance barriers to ease in making transactions. This research investigates several factors influencing BerryBenka customers’ intention to purchase, specifically, perceived product quality, e-service quality, and customer satisfaction. The method applied in this study is quantitative research by distributing questionnaires to the respondents as many as 136 people who have mobile phones, have access to connect to the internet, and have installed and purchased at least one from the BerryBenka application before. This study verified that perceived product quality has a significant influence on customer satisfaction and purchasing intention. E-service quality was also found to significantly influence purchasing intention, nevertheless, does not significantly influence customer satisfaction. Also, customer satisfaction significantly influences purchasing intention.